Analysis of the Mechanical Properties of SMAW welded Joints on API 5LX42 Steel Pipelines - Benhamel, Abdelhamid; Hadjoui, Fethi; Hadjoui, Abdelhamid (Engineering, Technology & Applied Science Research, 2025)
This paper examines the performance of gas pipeline welding in relation to the mechanical properties and metallurgical structure of the weld bead. Our research focuses on API 5L X42 steel pipes, which are commonly used for transporting hydrocarbons, particularly in the welded joints of these pipes. We conducted tests to characterize a weld created using the Shielded Metal Arc Welding (SMAW) method for gas pipelines. This included a microstructural analysis of the heterogeneous zone and the production of standardized specimens taken perpendicular to the welding direction, which were then subjected to uniaxial tension to assess the properties of both the base material and the filler metal under various stress conditions. Our findings indicate that the welded joint exhibits hardening compared to the base metal due to thermal effects, and we observed that the elongation in the welded specimens is significantly lower than that of the unwelded specimens.